The Effect of Female Leadership on Establishment and Employee Outcomes: Evidence from Linked Employer-Employee Data - Stefano Gagliarducci; M. Daniele Paserman (Institute for the Study of Labor (IZA), 2014)
In this paper we use a large linked employer-employee data set on German establishments between 1993 and 2012 to investigate how the gender composition of the top layer of management affects a variety of establishment and worker outcomes. We use two different measures to identify the gender composition of the top layer based on direct survey data: the fraction of women among top managers, and the fraction of women among working proprietors. We document the following facts: a) There is a strong negative association between the fraction of women in the top layer of management and several establishment outcomes, among them business volume, investment, total wage bill per worker, total employment, and turnover; b) Establishments with a high fraction of women in the top layer of management are more likely to implement female-friendly policies, such as providing childcare facilities or promoting and mentoring female junior staff; c) The fraction of women in the top layer of management is also negatively associated with employment and wages, both male and female, full-time and part-time. However, all of these associations vanish when we include establishment fixed effects and establishment-specific time trends. This reveals a substantial sorting of female managers across establishments: small and less productive establishments that invest less, pay their employees lower wages, but are more female-friendly are more likely to be led by women.
Keywords: D22; J16; J70; M50; 330; gender; firm performance; employer-employee data